Analysis of Competitive Strategy of Brown Sugar Makers in Marketing Based on Sharia Economic Perspective (Case Study of Brown Sugar Entrepreneurs in Amali District) - Arga Arya Ahmadil Awal; Arifin S; Kamiruddin (Yayasan Baru Haji Samsudin, 2024)
This research aims to analyze the competitive strategies of brown sugar producers in marketing within Amali District, Bone Regency, and to review these strategies from an Islamic economic perspective. The research method used is qualitative with a case study approach. Data collection was carried out through observation, interviews, and documentation. The results show that brown sugar producers in Amali District implement various competitive strategies in marketing, focusing on product quality, good service, and the application of comprehensive marketing concepts. They use the 4P marketing mix principle (Product, Price, Place, Promotion) in their business strategies. These entrepreneurs also demonstrate adaptability to various challenges such as limited stock, weather constraints, and capital limitations. From an Islamic economic perspective, the competitive strategies applied are in accordance with Islamic principles, based on the obligatory attributes of the Prophet and Messenger, namely Shiddiq (truthfulness), Amanah (trustworthiness), Fathanah (intelligence), and Tabligh (conveyance). This research implies the need for government support in the form of regulations and promotional programs, as well as efforts to improve product quality standardization and packaging to enhance the competitiveness of the local brown sugar industry.